Chapter 7 Urban ecosystem services and stakeholders - Heikkinen, Anna (Taylor & Francis, 2019)
This chapter argues that the discussion of urban sustainability is in urgent need of new understanding of how ecosystem services are generated in places where human and non-human stakeholders interact within the urban landscape. More than half of the world’s population currently lives in urban areas, and the rate of urbanisation is estimated to increase rapidly in the next three decades ( United Nations, 2014 ). This scale of urbanisation strains both urban and rural ecosystems, which are required to provide nutrition, clean water, fresh air, recreational opportunities, wellbeing and other life-supporting and life-enhancing opportunities to urban dwellers ( Chiesura and de Groot, 2003 ; Fischer and Eastwood, 2016 ; Standish, Hobbs, and Miller, 2013 ). Amidst such challenges as rapid urbanisation and abrupt climatic changes, ecosystem services are needed to provide the material and non-material benefi ts required to keep ever-growing cities liveable ( Alberti, 2016 ; Andersson et al., 2014 ; Finco and Nijkamp, 2001 ; Rees and Wackernagel, 1996 ). However, the current understanding of ecosystem services is inadequate, and the extant research has been criticised for both its anthropocentric bias and its focus on instrumental and monetary valuations of ecosystem services ( Pelenc and Ballet, 2015 ; Schröter et al., 2014 ). Moreover, the lack of a detailed elaboration of the socio-ecological interface of ecosystem services has resulted in the continued segregation of human and non-human processes in ecosystem service generation ( Andersson, Barthel, and Ahrné, 2007 ; Fischer and Eastwood, 2016 ; Maes et al., 2012 )